Long-Term Outcomes After Repair of Transurethral Perforation of Midurethral Sling. Issue 4 (July 2016) - Colhoun, Andrew; Rapp, David E.
Abstract : Objectives: The literature lacks long-term evaluation of outcomes after repair of transurethral midurethral sling (MUS) perforation. Methods: We prospectively followed 5 patients undergoing repair of urethral perforation (International Continence Society–International Urogynecological Association classification 4B) after MUS (mean follow-up, 54 months). Outcomes assessment was composed of validated measures of urinary (International Consultation on Incontinence Questionnaire [ICIQ]-Female Lower Urinary Tract Symptoms), vaginal (ICIQ-Vaginal Symptoms), and quality of life (Incontinence Impact Questionnaire, Short Form) symptoms. Results: Five patients underwent MUS (4 transobturator, 1 retropubic) with a mean of 41 months before referral. Primary referring complaints composed of hematuria (2), weak stream (2), and urgency (1). All but 1 patient reported transient urinary retention requiring catheterization after initial sling placement. Each patient underwent transvaginal sling excision and repair of urethral injury. Four of 5 patients experienced persistent postoperative stress urinary incontinence. Before final assessment, further treatment included observation, physical therapy, and autologous fascial sling in 1, 2, and 2 patients, respectively. ICIQ-Female Lower Urinary Tract Symptoms, ICIQ-Vaginal Symptoms, and Incontinence Impact Questionnaire, Short Form, assessment failed to demonstrate statistically significant improvements in comparison of baseline and multiple time point (6-week, 12-month, 54-month) assessments during long-term follow-up ( P > 0.05). Conclusions: Urethral perforation represents a significant complication after MUS placement. Many patients continue to have incontinence despite the use of physical therapy/salvage sling placement. Furthermore, subjective outcomes and quality of life do not seem to improve over time. Because of the rarity of urethral perforation, our small series is notable given the absence of reported data that include prospective, long-term follow-up with validated questionnaire evaluation. Abstract : Urethral perforation following mid-urethral sling is a significant complication, with long-term follow-up demonstrating persistent incontinence is common.